2019
DOI: 10.15332/iteckne.v16i2.2354
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of polylactic acid, polycaprolactone and Lay-Fomm 40 parts manufactured by fused deposition modeling, as a function of the printing parameters

Abstract: This study aims to determine the mechanical properties of parts manufactured by Fused Deposition Modeling (FDM) using three biocompatible polymer materials: Polylactic Acid (PLA), Polycaprolactone (PCL) and Lay-Fomm 40. Also, it was analyzed the influence of different printing parameters, material selection, infill percentage, and raster angle, over the mechanical properties. The samples were subjected to tension and compression tests using a universal testing machine, and elastic modulus, yield stress, and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…Additionally, we did not assess the impact of infill patterning on the mechanical strength of these scaffolds. However, our previous work [ 22 , 27 ] showed that LAY-FOMM60 is quite elastic with significantly lower mechanical strength than PLA, which is in agreement with other mechanical testing of these materials [ 29 , 30 , 31 ]. Even though this material was able to promote bone repair in a mandible defect, this would have to be considered for load bearing applications and regeneration in large bone defects.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, we did not assess the impact of infill patterning on the mechanical strength of these scaffolds. However, our previous work [ 22 , 27 ] showed that LAY-FOMM60 is quite elastic with significantly lower mechanical strength than PLA, which is in agreement with other mechanical testing of these materials [ 29 , 30 , 31 ]. Even though this material was able to promote bone repair in a mandible defect, this would have to be considered for load bearing applications and regeneration in large bone defects.…”
Section: Discussionsupporting
confidence: 86%
“…The fabrication of scaffolds for tendon and ligament tissue engineering has utilized numerous synthetic biomaterials, such as polycaprolactone, polyglycolic acid, poly(lactic-co-glycolic acid), poly-L-lactide, and polyurethane urea, as well as other techniques: electrospinning, knitting, melt extrusion-based 3D-bioplotting, and 3D braiding [ 13 , 30 ]. The technique of FDM in particular has been used to print different polymers to determine their tensile properties [ 43 ]. However, no studies to our knowledge have investigated raster angle in FDM printing to optimize biomaterial mechanics for ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Additive Manufacturing (AM) is a set of techniques used to join one or more materials to form objects from 3D topologies, generally layer by layer, instead of subtractive technologies such as mechanized cut, foundry, forging, and welding. One tremendous advantage for AM is that printing costs are virtually the same for one as for thousands of pieces [32], and it has excellent compatibility with different materials for constructing highly complex structures. The ISO/ASTM 52900 [9] categorizes the technologies Composite materials are intrinsically limited under localized impact loadings [18].…”
Section: Materials Extrusionmentioning
confidence: 99%